The effects and mechanisms of deep free trade agreements on agricultural global value chains - Huasheng Zeng; Shuyu Chen; Haoruo Zhang; Jinhai Xu (Frontiers in Sustainable Food Systems)
IntroductionIn the context of the growing global trend toward the deep integration of free trade agreements (FTAs), enhanced regional agricultural collaboration has significantly impacted the agricultural global value chains (AGVCs). Clarifying how FTA depth affects a country’s AGVC participation is crucial for promoting high-quality agricultural development and deepening international agricultural cooperation.Methods and goalsThis paper constructs and calculates indicators for FTA depth and the AGVC index, employing fixed effects models, PPML models, and other methods, aiming to empirically analyze how the depth of FTAs influences a country’s participation in AGVC and the mechanisms involved.ResultsThe findings indicate that an increase in FTA depth enhances a country’s degree of participation and position within the AGVC. Both the ‘WTO+’ and ‘WTO-X’ provision depth indices exert a significant positive influence on increasing participation and position within the AGVC, with the ‘WTO-X’ provision depth index demonstrating a more pronounced effect than the ‘WTO+’ provision. Furthermore, the positive effects of increased FTA depth on the integration of developed countries into the AGVC are greater than those on developing countries. Additional analysis reveals that FTA depth promotes trade liberalization and investment facilitation, thereby enhancing countries’ participation and position in the AGVC.DiscussionThe findings of this paper provide reliable empirical evidence for understanding the influence of FTA depth on AGVC and offer valuable policy insights for countries actively pursuing deeper FTAs.Policy recommendationsTo further advance the evolution of AGVC, it is recommended that countries actively promote the signing of deeper FTAs to accelerate trade liberalization and investment facilitation. At the same time, developed countries should strengthen agricultural technology research and development, assisting developing countries through technology transfer to jointly build a sustainable GVC; developing countries should enhance agricultural cooperation and improve their negotiating power in FTA discussions.